2021
DOI: 10.3390/geosciences11080314
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Deformation and Erosion during CME Evolution

Abstract: Magnetised coronal mass ejections (CMEs) are quite substantially deformed during their journey form the Sun to the Earth. Moreover, the interaction of their internal magnetic field with the magnetic field of the ambient solar wind can cause deflection and erosion of their mass and magnetic flux. We here analyse axisymmetric (2.5D) MHD simulations of normal and inverse CME, i.e., with the opposite or same polarity as the background solar wind, and attempt to quantify the erosion and the different forces that op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
2
6
1
Order By: Relevance
“…16 shows two peaks at the front of the flux rope in both cases. This contrasts with the CME structure simulated and analysed by Hosteaux et al (2021), which had only one peak at about the same distance from the Sun (at ≈35 R ). The first increase seen in our simulations can be attributed to the overlying magnetic field at the eruption time and to the streamer that is stripped away along with the CME.…”
Section: Propagation and Interaction Of Cmescontrasting
confidence: 74%
See 2 more Smart Citations
“…16 shows two peaks at the front of the flux rope in both cases. This contrasts with the CME structure simulated and analysed by Hosteaux et al (2021), which had only one peak at about the same distance from the Sun (at ≈35 R ). The first increase seen in our simulations can be attributed to the overlying magnetic field at the eruption time and to the streamer that is stripped away along with the CME.…”
Section: Propagation and Interaction Of Cmescontrasting
confidence: 74%
“…The first increase seen in our simulations can be attributed to the overlying magnetic field at the eruption time and to the streamer that is stripped away along with the CME. This would not be present in the case of Hosteaux et al (2021), who just injected a plasma blob into the solar wind and did not model the eruption. This suggests that different triggering mechanisms can affect the structure of CMEs, including during propagation, and therefore should be taken into consideration when interpreting CME structure.…”
Section: Propagation and Interaction Of Cmesmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from expansion, magnetic clouds can experience erosion during their propagation, stripping the ICME from magnetic field lines and causing a lower average magnetic field (Dasso et al, 2006;Ruffenach et al, 2015). Hosteaux et al (2021) showed that, in case of an inverse ICME (i.e. a CME with the same magnetic polarity as the background coronal magnetic field), the opposite occurs and magnetic field lines are added to the ICME, increasing the average magnetic field strength.…”
Section: Variation Of Icme Properties With Radial Distance From the Sunmentioning
confidence: 99%
“…Chen & Garren 1993;Cargill et al 1995). The few more recent studies of these physical processes include Shen et al (2012), who analysed the forces causing acceleration and deceleration of CMEs, and Hosteaux et al (2021), who studied the deformation and erosion of CMEs during their evolution. Furthermore, Kay & Nieves-Chinchilla (2021) presented the first results of their numerical code that simulates the propagation, expansion, and deformation of a CME in the interplanetary medium, and quantified the contributions of each of the imposed forces to these processes.…”
Section: Introductionmentioning
confidence: 99%